Moral Politics in the Philippines: Inequality, Democracy and the Urban Poor - Juliano, Hansley (Kasarinlan: Philippine Journal of Third World Studies; Vol 32 No 1,2 (2017): TWSC and Forty Years of Critical Scholarship, 2018)
Review of Moral Politics in the Philippines: Inequality, Democracy and the Urban Poor by Wataru Kusaka.